IMPACT OF SERVICE QUALITY AND DIGITAL MARKETING ON SALES GROWTH OF CREATIVE ENTERPRISES - Nurhaeni Sikki; Najmi Ihwani; Dadi Priadi (PT. Altin Riset Publishing, 2025)
This study investigates the impact of service quality and digital marketing on sales growth in creative enterprises, with a case study of the Kisah Hari Bandung start-up. The research aims to identify how these factors influence the achievement of sales targets and overall business performance. A quantitative survey method was applied with 99 respondents selected from a population of 4,224 consumers using probability sampling. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression. The findings reveal that service quality and digital marketing both have a positive and significant effect on sales growth, either individually or simultaneously. Together, these variables contribute 71.8% to sales growth, while the remaining proportion is influenced by other factors not examined in this study. The results highlight the importance of quality service delivery and effective digital marketing strategies for creative business sustainability.